Clinico-Demographic Characteristics of Cervical Spondylosis Patients Presented with Chest Pain (Journal of Current and Advance Medical Research, 2018)
Background:  The prevalence of non-cardiac chest pain is estimated to be more than 65.0% of all cases with chest pain.Objective: The objective of the present study was to see the clinic-demographics characteristics and investigational findings of cervical spondylosis patients presented with chest pain.Methodology: This cross-sectional study was carried out in the department of Physical Medicine & Rehabilitation at National Institute of Cardiovascular Disease (NICVD), Dhaka, Bangladesh from July 2012 to June 2013 for a period of one year. The diagnosis was made by detailed history, clinical examination and relevant investigations.Result: In this study, female (60%) were much more sufferer especially in much younger age group (41.67%). People from urban area (68.75%) and affluent status (41.67%) were more affected; also who were in anxiety-depressed state of mind (50%) and those who worked by neck bending posture (45.83%). All patients presented with chest pain (100%) & other associated symptoms like arm pain (41.67%), tingling sensation of left upper limb (22.91%), shoulder pain (25.0%) and scapular pain (16.67%). All (100%) patients had normal ECG finding. On the other hand, they (100.0%) had some finding in cervical spine X-ray; clinically the patient had painful neck movement (75.0%). A specific test for cervical radiculopathy “spurling maneuver” was positive in (22.91%).Conclusion: Through chest pain due to cervical disc disease widely reported but remains under recognized. So careful evaluation of patient for chest pain might have saved the patient for admission and various expensive invasive procedure.Journal of Current and Advance Medical Research 2018;5(2):55-59